TURATS SEBAGAI STRATEGI PEMBELAJARAN DI LEMBAGA PENDIDIKAN ISLAM - Fawaidil Wafa, Alfian; Kuswandi, Dedi (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2024)
Abstract. This research. aims to analyze how turats can be used in learning strategies in Islamic education institutions. This research uses the literature review method, which is a structured, clear and reproducible approach to identifying, evaluating and synthesizing research works and ideas that have been created by researchers and practitioners. The Turats learning model is experiencing dynamic development. In terms of learning methods, this model follows technological advances, while in the policy aspect, the focus is given to increasing teacher capacity and competency. The findings from this research state that learning the book of turats focuses on the reading aspect with an emphasis on halaqoh. Islamic educational institutions need to implement several steps to achieve progress in learning, and these efforts are initiated by inclusive school supervisors as leaders in each Islamic school. Islamic educational institutions can adopt this halaqoh method which teachers or ustad can apply in learning, where the ustad is responsible for guiding students in reading texts or memorizing, while providing correction if there are errors in pronunciation. Islamic educational institutions need to implement several steps to achieve progress in learning, and these efforts are initiated by inclusive school supervisors as leaders in each Islamic school. Apart from that, there are also efforts made by heads of Islamic education institutions, which of course cannot be separated from collaboration with Islamic school executives within them and asatidz operating under their supervision. Abstrak. Penelitian yang dilakukan ini bertujuan untuk menganalisis turats bisa digunakan di dalam strategi pembelajaran di lembaga-lembaga Pendidikan islam. Penelitian ini menggunanakan metode literaratur riview yang merupakan merupakan suatu pendekatan yang terstruktur, jelas, dan dapat direproduksi untuk menemukan, mengevaluasi, dan menyintesis hasil penelitian dan ide-ide dari peneliti dan pelaku. Model pembelajaran kitab turats mengalami perkembangan yang dinamis. Dalam hal metode pembelajaran, model ini mengikuti kemajuan teknologi, sementara dalam aspek kebijakan, fokus diberikan pada peningkatan kapasitas dan kompetensi pengajar. Temuan dari penelitian ini menyatakan bahwa pembelajaran kitab turats menitik beratkan pada aspek bacaan dengan penekanan pada halaqoh. Lembaga Pendidikan islam perlu mengimplementasikan beberapa langkah Untuk mencapai kemajuan dalam pembelajaran, dan pelaksanaan ini diprakarsai oleh pengawas sekolah inklusif sebagai pemimpin di setiap sekolah Islam. Lembaga Pendidikan islam bisa mengadopsi metode halaqoh ini dimana guru atau ustad bisa menerapkan di dalam pembelajaran, dimana ustad bertanggung jawab untuk membimbing siswa dalam membaca teks atau hafalan, sambil memberikan koreksi apabila ada kesalahan dalam pelafalan. Selain itu, ada juga usaha yang dilakukan oleh kepala lemabaga Pendidikan islam, yang tentunya tidak dapat dipisahkan dari kerjasama dengan eksekutif sekolah islam yang berada di dalamnya dan asatidz yang beroperasi di bawah supervisinya.